Impact of replacing red and processed meat with non-meat alternatives on metabolic health - Clark, Marie A. (2017)
Meat represents an important source of high quality protein and micronutrients. However, excessive consumption, particularly of red and processed meat, may increase risk of chronic diseases, including cardiovascular disease (CVD) and certain cancers. Meat production also represents an inefficient use of finite resources and may be rendered unsustainable by global population growth and the impact of climate change. This project assessed acute and chronic effects of replacing meat with non-meat alternatives on plasma lipids and lipoproteins, and other markers of cardiovascular health. Two postprandial trials were undertaken in which volunteers consumed two meals (with and without meat), of similar macronutrient content, at least one week apart. Blood was collected every 30 min, for up to 6h post-meal, and chylomicron (CM) and very low density lipoprotein (VLDL) were isolated. Results demonstrated the expected postprandial changes in CM and VLDL triacylglyceride (TAG) but no significant differences between the meat and non-meat meals were observed. The chronic effects of meat reduction on CVD risk were assessed in a single group, non-randomised, crossover design trial in which healthy volunteers reduced their red and processed meat intake by at least 50%. Volunteers were provided with a range of non-meat alternatives to facilitate the change in diet and aid compliance. Following a four week lead in period, they reduced their meat consumption, by at least 50%, and were assessed at six and 12 weeks. Fasting levels of serum lipids and lipoproteins were measured together with a range of anthropometric and physiological variables. Reducing meat consumption significantly lowered total serum and low density lipoprotein (LDL) cholesterol in males (P=0.009 and P=0.007 respectively) but not females. No significant differences were seen in any other measurements. In conclusion, replacing meat in the diet does not impact on postprandial lipid responses, but chronic replacement specifically reduces LDL cholesterol in males.